Luoghi di confine e tradizioni a contatto nel manoscritto Landau Finaly 149: filologia materiale per due volgarizzamenti del De mulieribus claris del Boccaccio - Tommasi, Alessia (Giornale storico della letteratura italiana, 2022)
Abstract The Landau Finaly 149 codex of the Biblioteca Nazionale Centrale in Florence is a unique specimen in that it binds together two codicological sections containing parts of two distinct translations into the vernacular of Boccaccio’s De mulieribus claris - the 14th-century work by Donato Albanzano and that of his contemporary, Antonio da Sant’Elpidio - which together form a single text. The first section contains Chapters 1 through part of 66 of Albanzani’s version, ending abruptly after the thirtieth folio; the subsequent folio belongs to the second section in question and resumes exactly where Albanzano’s translation left off, but with Sant’Elpidio’s version. After pointing out the unique codicological and textual features of the Landau codex, this article examines the two translations from a comparative perspective, delving into their ties to the Latin text and its different editions. Such an analysis has made it possible to determine that each vernacular version is linked to a distinct phase of De mulieribus claris, i.e. the sixth and seventh phases of the nine proposed by Vittorio Zaccaria.